The effect of blue-blocking intraocular lenses on circadian biological rhythm: protocol for a randomised controlled trial (CLOCK-IOL colour study). Issue 5 (12th May 2015) - Nishi, Tomo; Saeki, Keigo; Obayashi, Kenji; Miyata, Kimie; Tone, Nobuhiro; Tsujinaka, Hiroki; Yamashita, Mariko; Masuda, Naonori; Mizusawa, Yutarou; Okamoto, Masahiro; Hasegawa, Taiji; Maruoka, Shinji; et al.
Abstract : Introduction: Blue light information plays an important role in synchronising internal biological rhythm within the external environment. Circadian misalignment is associated with the increased risk of sleep disturbance, obesity, diabetes mellitus, depression, ischaemic heart disease, stroke and cancer. Meanwhile, blue light causes photochemical damage to the retina, and may be associated with age-related macular degeneration (AMD). At present, clear intraocular lenses (IOLs) and blue-blocking IOLs are both widely used for cataract surgery; there is currently a lack of randomised controlled trials to determine whether clear or blue-blocking IOLs should be used. Methods and analysis: This randomised controlled trial will recruit 1000 cataract patients and randomly allocate them to receive clear IOLs or blue-blocking IOLs in a ratio of 1:1. The primary outcomes are mortality and the incidence of cardiovascular disease, cancer and AMD. Secondary outcomes are fasting plasma glucose, triglycerides, cholesterol, glycated haemoglobin, sleep quality, daytime sleepiness depressive symptoms, light sensitivity, the circadian rhythm of physical activity, wrist skin temperature and urinary melatonin metabolite. Primary outcomes will be followed until 20 years after surgery, and secondary outcomes will be assessed at baseline and 1 year after surgery. Ethics and dissemination: Ethical approval has been obtained from the Institutional Review Board of Nara Medical University (No. 13-032). The findings of this study will be communicated to healthcare professionals, participants and the public through peer-reviewed publications, scientific conferences and the University Hospital Medical Information Network Clinical Trials Registry (UMIN-CTR) home page. Trial registration number: UMIN000014680.